Insulin Detemir Causes Lesser Weight Gain in Comparison to Insulin Glargine: Role on Hypothalamic NPY and Galanin - Mohammad Ishraq Zafar; Cuining Hu; Danfeng Liu; Raja Adeel Shafqat; Feng Gao (Journal of Diabetes Research)
Objective. Compared with other insulin analogues, insulin detemir induces less weight gain. This study investigated whether this effect was achieved by influencing the hypothalamic appetite regulators neuropeptide Y (NPY) and galanin (GAL). Methods. Type  2 diabetic rat models were established with a high-fat diet and intraperitoneal injection of STZ. All rats were divided into NC, DM, DM+DE and DM+GLA groups. Glycemic levels of all study groups were checked at study onset and after 4 weeks of insulin treatment. Food intake and body weight were monitored during treatment. After 4 weeks, the hypothalamus of rats was examined for NPY and GAL mRNA and protein expression. Results. After 4 weeks of treatment, compared with the DM+GLA group, the DM+DE group exhibited less food intake (P<0.05) and less weight gain (P<0.05), but showed similar glycemic control. The expression of hypothalamic NPY and GAL at both mRNA and protein level were significantly lower (P<0.05) in the DM+DE group. Conclusion. Insulin detemir decreased food intake in type 2 diabetic rats, which led to reduced weight gain when compared to insulin glargine treatment. This effect is likely due to downregulation of hypothalamic NPY and GAL.